Modelo de aprendizaje según Vygotsky. - García Crespo, Nadia Gisella (My University, 2019)
This paper aims to describe Lev Vygotsky's Learning Model, identify the main categories and principles of the model to determine how learning will occur in the individual according to Vygotsky's theory. A descriptive investigation was carried out, since the work focused on the collection of data through the bibliographic search of information, so that it is possible to describe the most characteristic, distinctive and particular aspects related to the object of investigation. The general learning norms are needed to give rise to the different psychological approaches that have intervened in their study, trying to explain their process. It begins with a brief description of the Behavioral theory of learning, then the Cognitivist theory and finally focuses on Constructivism, an approach from which Vygotsky's Historical-Cultural perspective emerges. Within the learning theory developed by Vygotsky, categories such as the Zone of Proximal Development, the Real Development Level, the Potential Development Level, the Developer Learning and the Mediation Principle stand out, which are indispensable factors that intervene in the acquisition of knowledge to the author. To finish the work, describe the effectiveness and usefulness of Lev Vygotsky's Learning Model in higher education.
El presente escrito pretende describir el Modelo de Aprendizaje de Lev Vygotsky, detallando las principales categorías y principios del modelo para determinar cómo se produce el aprendizaje en el individuo según la teoría de Vygotsky. Se realizó una investigación descriptiva, ya que el trabajo se centró en la recogida de datos a través de la búsqueda bibliográfica de información, de modo que se logre describir los aspectos más característicos, distintivos y particulares referentes al objeto de investigación. Se precisan definiciones generales de aprendizaje para dar lugar a los diferentes enfoques psicológicos que han intervenido en su estudio, intentando explicar su proceso. Se inicia con una breve descripción de la teoría Conductista del aprendizaje, seguidamente la teoría Cognitivista y finalmente se centra en el Constructivismo, enfoque del cual surge la perspectiva Histórico-Cultural de Vygotsky. Dentro de la teoría de aprendizaje desarrollada por Vygotsky se resaltan categorías como la Zona de Desarrollo Próximo, el Nivel de Desarrollo Real, el Nivel de Desarrollo Potencial, el Aprendizaje Desarrollador y el Principio de Mediación, que para el autor son factores indispensables que intervienen en la adquisición del conocimiento. Para finalizar el trabajo, se describe la eficacia y utilidad del Modelo de Aprendizaje de Lev Vygotsky en la educación superior.
Keywords: APRENDIZAJE; EDUCACION; VYGOTSKY